2013
DOI: 10.1093/infdis/jit433
|View full text |Cite
|
Sign up to set email alerts
|

Association of the IFNL4-ΔG Allele With Impaired Spontaneous Clearance of Hepatitis C Virus

Abstract: Interferon lambda 4 protein can be generated in IFNL4-ΔG carriers but not IFNL4-TT homozygotes. We studied 890 anti-hepatitis C virus (HCV)-positive participants in the Women's Interagency HIV Study. Among blacks (n = 555), HCV was more often cleared for those with genotype IFNL4-TT/TT (32.6%; odds ratio [OR], 3.59; P = 3.3 × 10(-5)) than IFNL4-TT/ΔG (11.3%; OR, 0.95; P = .86) or IFNL4-ΔG/ΔG (11.9%; referent). Pooling these data with published results in blacks (n = 1678), ORs were 3.84 (P = 8.6 × 10(-14)) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
80
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 10 publications
8
80
0
Order By: Relevance
“…Roughly, a quarter of HCV-infected individuals clear the virus spontaneously, this largely happens during the acute phase of the infection. Somewhat surprisingly, the genetic variations near the IFNL3 (IL28B) locus are also strongly associated with spontaneous clearance of HCV infection 13,14 . That points towards a pivotal role for IFNls in HCV clearance and a possible influence of IFNls on the adaptive immune response that is generated during the acute phase of HCV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Roughly, a quarter of HCV-infected individuals clear the virus spontaneously, this largely happens during the acute phase of the infection. Somewhat surprisingly, the genetic variations near the IFNL3 (IL28B) locus are also strongly associated with spontaneous clearance of HCV infection 13,14 . That points towards a pivotal role for IFNls in HCV clearance and a possible influence of IFNls on the adaptive immune response that is generated during the acute phase of HCV infection.…”
mentioning
confidence: 99%
“…A recent key discovery identified the IFNL4 gene and showed that a polymorphism (rs368234815), which causes the disruption of the IFNL4 reading frame, correlates with a substantially better treatment response 15,16 as well as better spontaneous clearance rate 13 . Thus, patients having a nonfunctional IFNL4 gene are more likely to clear the HCV infection.…”
mentioning
confidence: 99%
“…The majority of patients enrolled in the study were African-Americans, who are less likely to have the favorable genotypes CC, TT/TT, and GG at the rs12979860, rs368234815, and rs4803217 loci, respectively. Only 2 of 8 paired biopsies and 4 of 25 unpaired EOT liver biopsies were from patients with the favorable IFNL4 rs368234815-TT/TT genotype, the strongest marker associated with HCV clearance in AfricanAmericans (31,34). Due to high linkage disequilibrium between these markers, the genotypes for the 2 other markers were correlated.…”
Section: Resultsmentioning
confidence: 99%
“…Bilbert et al reported that induction of IL28B expression is associated with novel TT/ΔG polymorphism ss469415590, which is a better predictor of HCV clearance than rs12979860 [42]. Aka et al studied HIV-positive black women, and found that HCV was cleared in 32.6% of the women with the IFNL4 genotype TT/TT, by comparison with TT/ΔG and G/ΔG genotypes (11.3% and 11.9%, respectively) [43].…”
Section: Ifnl4 and Il28b Polymorphismmentioning
confidence: 99%